A small macro-econometric model of the Cambodia economy - Sovannchakriya, So
Abstract (This thesis aim to capture the fundamental structure of the Cambodia economy through the construction and simulation of a small scale macroeconomics model (SSMM). An SSMM is an aggregated model with considerable theoretical content that contains far fewer equations that large-scale macroeconomic models and provides direct analytical solutions. This study involves the use of a macro econometric model for nonstationary annual time series data from 1994 to 2015 to analyze of the Cambodia economy. The main intension in this study is to facilitate the need for forecasting simulation. The model comprises household final consumption expenditure, government final consumption expenditure, gross fixed capital formation, import and export. The equilibrium-correction form (ECM) is used for all the behavioral equations and the general simple dynamic specification approach is adopted. Great efforts have been made to achieve the best possible blend of standard long-run theories, country-specific institutional features and short-run dynamics in data. The tracking performance of the model is evaluated. Validity of the model is checked both within the sample and out of sample cases).